Update on Antiviral Strategies Against COVID-19: Unmet Needs and Prospects - Liu, Ching-Hsuan; Lu, Cheng-Hua; Wong, Shu Hui; Lin, Liang-Tzung (Frontiers in Immunology, 2021)
By December 2020, the COVID-19 pandemic had caused more than 74 million confirmed cases and 1.6 million related deaths around the world. However, only a few drugs have been approved in certain areas and for use in conditional patients, and the vaccine candidates were only recently approved or authorized for emergency use without being fully implemented worldwide, suggesting that we are yet to reach effective control of the current outbreak as its uninhibited transmission continues precariously. Over the past few months, several therapeutic candidates have been proven ineffective in large clinical trials, while some other agents exhibited promising preliminary results. Meanwhile, the investigation of SARS-CoV-2-specific antivirals is underway. Despite still being preclinical, these agents could be beneficial for the long-term control of COVID-19 and deserve more research focus. In this article, we update the current status of therapeutic candidates that have been examined for COVID-19 management, including the virus-targeting inhibitors and host-targeting agents, with their antiviral efficacy in vitro, in vivo, and in clinical studies. Finally, we highlight the current challenges and future prospect of developing potent therapeutic agents against COVID-19.